Мовознавчі аспекти творчості Г. Хоткевича: стан, перспективи - Подолянчук, О. (Філологічний дискурс, 2019)
У статті розглядаються погляди вчених на означену
проблематику, визначено стан та перспективи її розвитку, що
дасть змогу в подальшому глибше дослідити індивідуальний стиль
письменника. З’ясовано проблеми, що виникають під час вивчення
індивідуального стилю письменника. Зокрема це питання біографії
поета, його світогляд, дослідження мистецької спадщини, вивчення
майстерності та стилю, фонетичних, морфологічних, лексичних та синтаксичних визначальних рис творів письменника. Проблема
дослідження художньої майстерності письменника, особливостей його
творчості, незважаючи на те, що вимірюється тисячами назв, і сьогодні постає як нова й актуальна. Відзначено, що більшість робіт,
де опрацьовані лінгвістичні досягнення Гната Хоткевича, спрямована на функціонально-стилістичне витлумачення мовних явищ, які є
характерними для художнього мислення письменника і становлять стилістичне ядро його творчості. The article provides a views of scientists on the marked problems, determine the
status and prospects of its development, which will make it possible in the future to
further study the individual style of the writer. The linguistic aspects of Hnat
Khotkevych's work are determined. The problems which arise during the study of
the individual style of the writer are revealed. In particular, this is the question of
the poet's biography, his outlook, the study of artistic heritage, the study of skill and
style, phonetic, morphological, lexical and syntactic defining features of the writer's
works. The problem of studying the literary skill of the writer, the peculiarities of his
work, despite the fact that it is measured by thousands of titles, appears today as
new and relevant. The artist's style is studied from different positions and from
different angles of view. It is noted that most of the works devoted to the linguistic
achievements of Hnat Hotkevich are aimed at the functional-stylistic interpretation
of language phenomena that are characteristic of the writer's artistic thinking and
constitute the stylistic core of his work. The creative and scientific heritage of the
Ukrainian prosperity of Hnat Hotkevich is based on solid methodologies, concepts,
innovative ideas, and the study of systematization of knowledge in the various
sectors of education, science and culture of Ukraine at the turn of the two epochs.
Phenomenonity of Hnat Martynovich was formed in difficult and difficult conditions
of personal and social life, wandering, persecution by pro-government structures, the
prohibition of publishing their works, sometimes the deprivation of elemental means
of subsistence in the form of baking cards, and finally - the desperate attempt by the
artist to surrender total repressions to the Soviet regime. The originality and uniqueness of its scientific research and creative heritage are invaluable, since they have played a significant role in the development of Ukrainian culture for centuries. Extremely large talent of creative personality of Khotkevych was in Ukrainian prose.